Outstanding Surgeon and Scientist Dmitry Alekseevich Arapov - S. A. Kabanova; Yu. S. Goldfarb; P. M. Bogopolsky; S. S. Petrikov; M. L. Rogal; P. A. Yartsev; V. I. Sleptsov (Неотложная медицинская помощь)
In 2022, we are approaching 125 years since the birth of Dmitry Alekseevich Arapov, a prominent domestic surgeon, scientist, experimenter, organizer of the military medical services. Dmitry A. Arapov, one of the most prominent representatives of the S.S. Yudin scientific school, worked at the N.V. Sklifosovsky Research Institute for Emergency Medicine from 1929 till 1984. He quickly proved himself not only as an excellent doctor and a skilled surgeon, but also as a researcher, and soon became one of the closest students and associates of S.S. Yudin. Dmitry A. Arapov drafted as a field surgeon during the Soviet-Finnish war of 1939-1940, from the first to the last day he went through the Great Patriotic War, being the Head of the surgical service of the Northern Fleet in Polyarny. In this position, he significantly improved the system for providing emergency surgical care on ships and in naval hospitals, based on the experience gained over the years of work at the N.V. Sklifosovsky Research Institute for Emergency Medicine. From July 1950 Dmitry A. Arapov was Chief Surgeon of the USSR Navy, from May 1953 he was Deputy Chief surgeon of the Main Military Sanitary Directorate of the USSR Ministry of Defense, and from May 1955 again Chief Surgeon of the USSR Navy, until his retirement in October, 1968. At the same time, Dmitry A. Arapov did not leave his work at the N.V. Sklifosovsky Research Institute for Emergency Medicine until the last days of his life. Dmitry A. Arapov is the author of more than 200 research papers, including 14 monographs. Scientific interests of Dmitry A. Arapov went far beyond emergency surgery, to which he naturally paid most attention. His works are devoted to various issues of military and emergency surgery of the abdominal and thoracic organs, topical issues of burn injuries, surgical site infections, reconstructive surgery, neurosurgery, treatment of endocrine disorders, and anesthesiology and resuscitation. Also Dmitry A. Arapov successfully dealt with the problems of autotransfusion, blood reinfusion from the chest and abdomen, transfusion of fibrinolytic blood. The main directions of scientific research, laid down by Dmitry A. Arapov, are currently being continued at the Scientific Department of Emergency Surgery, Endoscopy and Intensive Care of the N.V. Sklifosovsky Research Institute for Emergency Medicine. Memory of Dmitry A. Arapov has been preserved to this day. To the 100th anniversary of the birth of D.A. Arapov, a scientific conference was held at our Institute. The naval hospital in the town of Polyarny, Murmansk region, was named after Dmitry A. Arapov, and in honor of D.A. Arapov, a memorial plaque was installed on its building. In the 70s of the twentieth century, People’s Artist of the USSR L.E. Kerbel created a sculpture of Dmitry A. Arapov, which was stored in the local history museum of the town of Polyarny. His bust portrait (by artist T.S. Smagina) is exhibited at the Scientific Department of Emergency Surgery, Endoscopy and Intensive Care of the N.V. Sklifosovsky Research Institute for Emergency Medicine. In addition, the N.V. Sklifosovsky Research Institute for Emergency Medicine owns an earlier portrait of Dmitry A. Arapov by artist F.S. Bulgak. We introduce these portraits into scientific circulation for the first time. We are confident that they will be able to tell contemporaries a lot about this scientist, surgeon and man who made a great contribution to surgery and military medicine, and rightfully entered the history of Russian medicine.